2012
DOI: 10.1002/mds.25006
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation site within the MRI‐defined STN predicts postoperative motor outcome

Abstract: High-frequency stimulation of the subthalamic nucleus (STN-HFS) is highly effective in treating motor symptoms in Parkinson's disease (PD) and medication side effects as well as in improving quality of life. Despite preoperative screening for patients as eligible candidates for this treatment, electrode position may furthermore influence treatment quality. Here, we investigated the relationship between the anatomical site of stimulation within the MRI-defined STN and the outcome of PD patients after STN-HFS. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
105
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 143 publications
(117 citation statements)
references
References 11 publications
10
105
0
Order By: Relevance
“…Our finding of the median of the optimal stimulation sites in the dorso-lateral STN agrees with reports that stimulation in the dorso-lateral STN [5,22] improves motor symptoms in PD patients. …”
Section: Limitations In Targeting Electrode Placement and Reconstrucsupporting
confidence: 92%
See 1 more Smart Citation
“…Our finding of the median of the optimal stimulation sites in the dorso-lateral STN agrees with reports that stimulation in the dorso-lateral STN [5,22] improves motor symptoms in PD patients. …”
Section: Limitations In Targeting Electrode Placement and Reconstrucsupporting
confidence: 92%
“…DBS has become a standard treatment for patients with advanced Parkinson's disease (PD). For many patients a site within the subthalamic nucleus (STN) is chosen as an efficient target site to improve motor symptoms [3,5,6,22].…”
Section: Introductionmentioning
confidence: 99%
“…DBS has been used successfully for many years in movement disorders such as Parkinson's disease (PD), [1][2][3] yet treatment may sometimes be suboptimal for several different reasons, such as inappropriate patient selection or programming or electrode placement; two referral centers for DBS troubleshooting have reported that therapy failure in half of the evaluated leads was caused by suboptimal positioning. 4 Stimulation of the dorsolateral subthalamic nucleus (STN) is associated with best motor symptom control, 5,6 but excessive stimulation of adjacent fiber tracts can cause adverse effects such as disturbances in speech and fine-motor control. 7,8 Small lead deviations from the intended functional target play an important role in suboptimal efficacy 6 and side effects, 9 even in experienced surgical centers.…”
Section: Clinical Opportunitiesmentioning
confidence: 99%
“…4 Stimulation of the dorsolateral subthalamic nucleus (STN) is associated with best motor symptom control, 5,6 but excessive stimulation of adjacent fiber tracts can cause adverse effects such as disturbances in speech and fine-motor control. 7,8 Small lead deviations from the intended functional target play an important role in suboptimal efficacy 6 and side effects, 9 even in experienced surgical centers. 6 Even with a seemingly optimal lead position, functional targets vary from patient to patient, and axial displacements may still lead to adverse effects.…”
Section: Clinical Opportunitiesmentioning
confidence: 99%
See 1 more Smart Citation